Genetic analysis Of self-incompatibility in Petunia and Stumberger - Abdulla, Mohamed (2025)
Self-incompatibility (SI) is a widespread genetic mechanism which prevent self-fertilization in angiosperms. The genus Petunia of the Solanaceae serve as a model for SI research due to its short life cycle and accessible floral morphology. In Petunia, SI is mediated by S-RNase dependent degradation of self-pollen RNA within the style, arresting pollen tube growth. Breakdown of SI confers self-compatibility (SC), with implications for breeding and yield optimization.